SOCIAL INTERACTIONS AND INSTRUCTIONAL PRACTICES AMONG ENGLISH AS FOREIGN LANGUAGE TEACHERS: LESSONS FROM TRENDS IN BENIN REPUBLIC - Hounhanou, Arlette Joséline Viviane (My University, 2018)
This study examined Social Interactions on Instructional Practices among EFL Teachers in some secondary schools in Benin Republic. The concurrent research design informed the methodological consideration of the study. A sample size of seventy- seven 77 teachers of English was used. The instruments used for data collection were questionnaire and interview guide. The questionnaire data were put into frequencies and percentages while the interview data were analyzed into themes based on the research questions. The study revealed four types of EFL teachers’ interactions. These included collaboration, individualism, contrived collegiality and balkanization. The study also established that social interactions influenced EFL teachers’ instructional practices. It is important for instructional leaders to ensure that social interactions among teachers continue to be appropriate to enhance the effective teaching and learning of the language of English.
Keywords: EFL balkanization. teachers; social interactions; Instructional Practices